2005
DOI: 10.1128/cdli.12.10.1235-1237.2005
|View full text |Cite
|
Sign up to set email alerts
|

Immunoglobulin A Antibody Responses in Dengue Patients: a Useful Marker for Serodiagnosis of Dengue Virus Infection

Abstract: We determined the usefulness of an immunoglobulin A (IgA) antibody-capture enzyme-linked immunosorbent assay for serodiagnosis of dengue virus infections. The results indicate that the presence of IgA and IgM in serum samples assures recent primary dengue virus infection even with a single serum sample.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 6 publications
1
18
0
Order By: Relevance
“…Our results demonstrate that IgA is a reliable marker for dengue diagnosis. Previous studies have shown the diagnostic utility of IgA in serum principally in secondary cases 3,9,10,20 ; here, sensitivity was greater in secondary cases as well (98% in secondary versus 90% in primary cases). Interestingly, in contrast to serum and filter-paper blood spots, detection of IgM and IgA in saliva was greater in primary than in secondary dengue cases.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Our results demonstrate that IgA is a reliable marker for dengue diagnosis. Previous studies have shown the diagnostic utility of IgA in serum principally in secondary cases 3,9,10,20 ; here, sensitivity was greater in secondary cases as well (98% in secondary versus 90% in primary cases). Interestingly, in contrast to serum and filter-paper blood spots, detection of IgM and IgA in saliva was greater in primary than in secondary dengue cases.…”
Section: Discussionmentioning
confidence: 83%
“…Traditionally, diagnosis and epidemiologic surveillance relies on detection of DENV-specific IgM antibodies in serum of suspected dengue cases, 2,3 while the incidence of DENV infection is determined by detecting DENV-specific IgG or total antibody in serum via ELISA or the time-consuming and cumbersome hemagglutination inhibition or plaque reduction neutralization test (PRNT) assays. [4][5][6][7][8] A few studies have evaluated the use of anti-DENV IgA as a dengue diagnostic marker [9][10][11] ; others have assessed alternatives to serum as diagnostic specimens. 9,[11][12][13] However, no comprehensive studies of multiple immunoglobulin classes and different types of biological samples have been reported, especially in relation to measuring incidence of DENV infection.…”
Section: Introductionmentioning
confidence: 99%
“…High homology between dengue serotypes and recognition of common epitopes, during a sequential could explain the IgM levels detected in our cases. Dengue IgA antibody detection in serum samples from individuals with dengue infections have been proposed as a serological marker for diagnosis [9] [39] and as an indicator of recent infection [40] [41]. In this study, highest IgA ratios were observed for secondary D and SD cases and mainly in samples collected after defervescence day.…”
Section: Discussionmentioning
confidence: 56%
“…11 Our study confirms that anti-dengue IgA may also be a useful marker of dengue infection in capillary blood samples. 11,13,34 However, our results raise important questions regarding this assay. Indeed, IgA could not be detected in four patients infected by DENV-1 serotype, suggesting that the sensitivity of the IgA detection assay in capillary samples may depend on the virus serotype.…”
Section: Discussionmentioning
confidence: 56%
“…[4][5][6][7][8][9] From day 5 on (early convalescent phase), it is recommended to use serological tests that can detect dengue virus-specific immunoglobulin M (IgM) and IgA. [10][11][12][13] Second, a venous blood sample is required, and such samples may be difficult to collect, store, and transport to specialized diagnostic laboratories, particularly for children and patients living in remote areas. Therefore, other alternatives for dengue diagnosis based on non-invasive sample collection combined with sensitive, specific, rapid, and cost-effective detection tools are required to identify and manage patients suspected of dengue; such tools would also be useful for field studies in endemic regions.…”
Section: Introductionmentioning
confidence: 99%